2016
DOI: 10.5694/mja16.00287
|View full text |Cite
|
Sign up to set email alerts
|

Estimating non‐billable time in Australian general practice

Abstract: Most GPs spend a significant amount of unpaid time on patient care between consultations, an inherent problem of the fee-for-service system. This work should inform discussions of future funding models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The popularity of home visits may be in part due to the lack of alternative options to access GPs outside of the traditional format. For example, though mentioned in our study, over-the-phone consultations are a non-billable service and not often done by GPs [33]. While there is some debate surrounding the overall cost and cost-effectiveness of GP home visits, it is clear that they are preferred by patients in the context of having few other options.…”
Section: Discussionmentioning
confidence: 91%
“…The popularity of home visits may be in part due to the lack of alternative options to access GPs outside of the traditional format. For example, though mentioned in our study, over-the-phone consultations are a non-billable service and not often done by GPs [33]. While there is some debate surrounding the overall cost and cost-effectiveness of GP home visits, it is clear that they are preferred by patients in the context of having few other options.…”
Section: Discussionmentioning
confidence: 91%
“…7 A substudy of the Bettering the Evaluation and Care of Health (BEACH) program in 2012-14 reported an average of 2.5 hours per week. 5 Woolhandler and Himmelstein's study of US primary care physicians found that 17.3% of their work was 'patient care activities outside of office visits' (termed 'AOVs') and that a higher amount of this work was associated with lower job satisfaction. 14 However, the findings are lower than the estimates reported by several studies that used observational rather than self-reported methods to obtain data.…”
Section: Amount Of Non-billable Workmentioning
confidence: 99%
“…This work includes coordinating patient care (eg managing investigation results or liaising with specialists or patients' families) or performing administrative tasks to meet personal and practice management requirements. [3][4][5] In 2017, it was estimated that 20% of Australian GPs' time is spent on this non-face-to-face work; 6 however, previous studies have provided estimates ranging from zero hours to more than nine hours per week. 5,7 Female practitioners report spending more time on these tasks, as do those managing patients who are elderly or have a chronic disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations